Human resource planning management in the construction of mitha pre-marriage healthcare and aesthetic clinic - Damanik, Rani; Kustiawan, Unggul; Indradewa, Rian; Dhafi Iskandar, Muhammad (Jurnal EduHealth, 2024)
This research aims to analyze the role of human resource planning management in the development of KLINIK MITHA, which specifically focuses on pre-wedding and aesthetic health services. The research method involved a qualitative approach by conducting a detailed case study of KLINIK MITHA, which involved in-depth interviews with the human resource manager, clinic owner, and relevant staff. Data analysis was conducted using content analysis techniques to identify key patterns related to human resource planning management. The results showed that effective human resource planning management plays a key role in the development and operationalization of KLINIK MITHA. Aspects such as selective recruitment, staff training and development, and targeted performance appraisals have a significant impact on service quality and business sustainability. In addition, alignment between staff needs and the clinic's strategic goals is also a key factor in successful human resource management. The conclusion of this study is that well-focused and integrated human resource planning management contributes positively to the development and operation of KLINIK MITHA. The findings provide business practitioners and clinic owners with an in-depth understanding of the importance of effective human resource management in managing health and aesthetic clinics. The practical implication of this study is that careful implementation of human resource planning management practices can improve clinic performance and provide a competitive advantage.